Modeling hyperthermal events in the Mesozoic-Paleogene periods: a review - Zhang, Yinggang; Mills, Benjamin J. W.; He, Tianchen; Hu, Xiumian; Zhu, Maoyan (Frontiers in Ecology and Evolution, 2023)
Hyperthermal events, which are characterized by rapid and extreme warming, occurred at several points throughout the Mesozoic to Paleogene periods. Model simulation studies have been conducted to investigate the mechanisms behind these events, including the carbon fluxes required to drive observed warming and isotope dynamics, the impact of warming on continental weathering, seawater pH, ocean anoxia, and the mechanism that terminated the warming.Studies using simple box models, Earth system box models, or 3D Earth system models have suggested that warming had a significant biogeochemical impact and would enhance continental weathering, increase ocean anoxia, and drive marine acidification. However, the magnitudes of these impacts remain debated and require further modeling work, as do the reconstructions of carbon fluxes and compositions.This review provides an overview of the current state of knowledge on hyperthermal events and proposes possible modeling development directions to better understand the causes and impacts of these events. Particularly, new long-term 'semispatial' Earth system models are promising tools for providing new solutions and perspectives on the biogeochemical responses to warming events and the carbon fluxes behind hyperthermal events from the Mesozoic to Paleogene periods.